Transcatheter Closure of Traumatic Ventricular Septal Defects: Two Cases and a Review of the Literature - Pham, Tai H; Glassy, Matthew S; Singh, Gagan D; Rogers, Jason H (Cardiology and Cardiovascular Medicine, 2022)
Abstract not available in the source database.